Pengaruh Work Readiness terhadap Quarter Life Crisis pada Fresh Graduate - Azmi, Nafizahtul; Nurmina, Nurmina (Lembaga Yasin AlSys, 2025)
This study aims to analyze the effect of work readiness on the quarter-life crisis among 2024 fresh graduates in Padang City. A quantitative approach was employed, involving 150 fresh graduates selected through purposive sampling based on the criteria of graduating in 2024, being unmarried, and currently unemployed. Data were collected using two instruments: the quarter-life crisis scale developed by Hasyim (2024) and the work readiness scale by Wijayanti (2019). Data analysis was conducted using simple linear regression. The results show a significance value of 0.000 (p < 0.05) with a regression coefficient of −0.264, indicating a significant negative effect between work readiness and the quarter-life crisis. These findings suggest that the higher the level of work readiness, the lower the level of quarter-life crisis experienced by 2024 fresh graduates in Padang City.